The Role of the Police in Criminal Mediation - El-Kady, Ramy (International Journal of Police Science, 2025)
This article highlights the role of the police in criminal mediation as one of the means used by the police in combatting crime and strengthening its social role using community policing. The research concluded a series of findings, notably the possibility of using criminal mediation to strengthen the concept of community policing and the recommendation that the proposed legislative amendments to the conciliation regime should be made to allow police officers to assume their role as intermediaries for the settlement of criminal disputes in criminal proceedings.